العالقات العامة الرقمية و تحسين صورة المؤسسة - لواش, أسماء; مختارية, كرطية (كلية العلوم الاجتماعية, 2025)
تُعدّ العلاقات العامة الرقمية من أحدث المفاهيم المعاصرة في إدارة سمعة المؤسسة في ظل التطور التكنولوجي والذكاء الاصطناعي، حيث تتيح التفاعل المباشر ضمن توجهاتها الاستراتيجية المبنية على بنية الإدارة الإلكترونية مع الجمهورين الداخلي والخارجي، سواء كان ذلك في إطار البيئة الحاضنة أو في التعامل مع المؤسسات الرسمية الأجنبية، وذلك بهدف تحسين الصورة الذهنية والتعريف بهوية المؤسسة المعنية. وتُعد العملية الاتصالية عنصرًا أساسيًا ومركزيًا في تحقيق الأهداف المرجوة، من خلال تعزيز التماسك بين الهياكل والأفراد والجماعات، إذ أصبحت مرتبطة بمدى التواصل بين الهياكل الرسمية، لا سيما مع ازدياد الدور الوظيفي للعلاقات العامة والتوسع الكبير في حجمها البنيوي في ظل التحول الرقمي الذي تشهده المؤسسات في الجزائر. وقد كشفت الدراسة الميدانية التي أُجريت على مؤسسة "هيبروك" بمنطقة وهران عن عمق هذا الموضوع. Digital public relations is one of the most contemporary concepts in managing an organization's reputation in the era of technological advancement and artificial intelligence. It enables direct interaction through strategic directions based on the structure of electronic management with both internal and external audiences, whether within the incubating environment or in dealing with official foreign institutions. This aims to improve the mental image and promote the identity of the concerned organization. The communication process is considered essential and central to achieving the desired objectives by enhancing cohesion among structures, individuals, and groups. It has become closely linked to the level of communication between official structures, especially with the growing functional role of public relations and the significant structural expansion it has witnessed within the context of digital transformation in Algerian institutions. The field study conducted at the "Hyproc" company in the Oran region highlighted the depth and relevance of this issue.
Keywords: العلاقات العامة، المؤسسة الرقمية، البنائية الوظيفية، العملية الاتصالية